Recent developments in high-strength Mg-RE-based alloys: Focusing on Mg-Gd and Mg-Y systems - Jinghuai Zhang; Shujuan Liu; Ruizhi Wu; Legan Hou; Milin Zhang (Journal of Magnesium and Alloys, 2018)
Higher strength is always the goal pursued by researchers for the structural materials, especially for the lightweight magnesium (Mg) alloys which generally have relatively low strength at present. From this aspect, the present paper reviews the recent reports of a kind of Mg alloys, i.e. Mg-RE (RE: rare earths, mainly Gd or Y) casting and wrought alloys, which have been able to achieve high strength compared with common or commercial Mg alloys, from the viewpoint and content of the alloy system, alloying constitution, preparation process, tensile strength and each of the main strengthening mechanisms. This review of recent research and developments in high-strength Mg-RE alloys is beneficial for the further design of Mg alloys with higher strength as well as excellent comprehensive performance. Keyword: Mg alloys, High strength, Rare earths (RE), Strengthening mechanism